2nd International Symposium on Gait and Balance in Multiple Sclerosis: interventions for gait and balance in MS. (June 2014) - Zackowski, Kathleen M.; Cameron, Michelle; Wagner, Joanne M.
Abstract Purpose: To provide a review of the 2nd International Symposium on Gait and Balance in Multiple Sclerosis (MS), emphasizing interventions in gait and balance for people with MS. Method: Review of current research on interventions used with people having MS and with people having other disorders that may provide novel insights into improving gait and balance and preventing falls in people with MS (pwMS). Results: Nine speakers provided evidence-based recommendations for interventions aimed at improving gait and balance dysfunction. Speaker recommendations covered the following areas: balance rehabilitation, self-management, medications, functional electrical stimulation, robotics, sensory augmentation, gait training with error feedback and fall prevention. Conclusions: The causes of gait and balance dysfunction in pwMS are multifactorial and therefore may benefit from a wide range of interventions. The symposium provides avenues for exchange of evidence and clinical experience that is critical in furthering physical rehabilitation including gait and balance dysfunction in MS. Implications for Rehabilitation Approaches to improve Gait and Balance dysfunction in Multiple Sclerosis. Balance exercises that include training of sensory strategies. Self-management and self-management support. Pharmacologic intervention, such as Dalfampradine. Functional electrical stimulation that may provide the extra stimulation to influence coordinated leg movements needed for walking.